INFORMATIONAL TECHNOLOGIES USAGE INFLUENCE ON ELDER SCHOOL AGE PUPILS PSYCHIC HEALTH STATE - Соколенко, В.М.; Зіненко, В.Є.; Лещенко, І.В.; Ткаченко, О.В.; Юдіна, К.Є. (World of Medicine and Biology, 2016)
Informational space globalization, computer technologies wide management by youth, educational establishments informatization level growth requires new approach to non-formed personality safety problem in a global informational environment. Computer technologies intensive introduction in life all spheres leads to new problem appearance – dependence on computer usage. Internet-dependence treatment technologies are at development stage in Ukraine.The work aim – investigating the informational technologies influence on psychic health state of the the Ist-IIIrd degrees Poltava secondary school N.19, named by A.Mironenko, 10-11-formed pupils.Sleeping duration and quality represents one of the psychic health indices. It was established by our survey results that 57% of the guys and 53% of the girls slept quietly and strongly while 19% of the guys and 29% of the girls marked that sleeping was very non-quiet in them, they could awake several times, speak, some of them even walked during their sleeping. The pupils biggest amount link this with overloadings at school or intensive trainings but some of them say that it occurs due to long time spending near the computers (videogames as well movies watching) or TV. We determined in a course of our survey that 10% of guys and 18% of the girls saw nightmares. Nightmares only sometimes appear in night dreams seldom to other 41% of the girls and 38% of the guys. A human being can live through the real life events for stress events avoiding. Psychic health is in a tight connection with a personality social welfare that is reflected in the following characteristics: social reality adequate perception, interest to surrounding world and social welfare; directness to public deed, consumption culture, altruism, responsibility before others and so on. It is worthy to mention that changings in the elder schoolchildren psychic health state find their reflection not only in the nervous processes major features indices corresponding shifts but in personal features dynamics and in intellectual activity as well.
Keywords: computer technology; young people; psihicheskoe health